Illegal Oil Bunkering and Environmental Degradation in Rivers State - Aniugbo Chijioke (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study investigated the impact of illegal oil bunkering on insecurity in Rivers State between 2007 and 2024, with particular emphasis on its environmental consequences. Anchored on the Marxian Political Economy Approach, the study explained how economic deprivation, inequality, and exploitation within the oil-rich Niger Delta have contributed to the persistence of illegal oil bunkering. The study adopted a combination of descriptive and historical research designs, utilizing both primary data (Key Informant Interviews and Focus Group Discussions) and secondary data from relevant literature and institutional reports. Data were analyzed using content and thematic techniques. Findings revealed that illegal oil bunkering has significantly contributed to environmental degradation through oil spills, destruction of farmlands, contamination of water sources, and loss of biodiversity. The study also found that black soot resulting from illegal refining has severely polluted the air, leading to increased cases of respiratory diseases, cancer risks, and other health challenges among residents. Furthermore, the destruction of ecosystems has undermined agriculture and fishing, thereby worsening poverty and socio-economic conditions in affected communities. The study concluded that illegal oil bunkering poses a serious threat to environmental sustainability, public health, and economic stability in Rivers State. It recommended stricter enforcement of environmental regulations, provision of alternative livelihoods for youths, and comprehensive environmental remediation and health interventions to address the adverse effects.